3D electrical resistivity of Gran Canaria island using magnetotelluric data. (January 2021) - Ledo, J.; García-Merino, M.; Larnier, H.; Slezak, K.; Piña-Varas, P.; Marcuello, A.; Queralt, P.; Pérez, N.M.; Schmincke, H.-U.; Sumita, M.
Highlights: New broad band magnetotelluric data covering the whole Gran Canaria island. First 3D electrical resistivity model of Gran Canaria island at crustal scale. Low resistivity anomalies found may be of interest for geothermal exploitation. 3D electrical resitivity shows a good correlation with other geophysical data available at crustal scale. Abstract: Gran Canaria, one of the two main islands of the Canary Archipelago off NW Africa, has been volcanically active for at least 15 million years. The island went through several volcanic cycles that varied greatly in composition and extrusive and intrusive activity. The complex orography of the island has excluded extensive land geophysical surveys on the island. A review of the available geophysical information on the island shows that it has been obtained mainly through marine and airborne geophysical surveys. A new dataset comprising 100 magnetotelluric soundings acquired on land has been used to obtain the first 3D electrical resistivity model of the island at crustal scale. The model shows high resistivity values close to the surface in the exposed Tejeda Caldera that extends at depth to the SE cutting the islands in half. Outside the inferred limits of the Tejeda Caldera the 3D model shows low resistivity values that could be explained by hydrothermal alteration at deeper levels and the presence of marine saltwater intrusion at shallower levels near the coast. The presence of unconnected vertical-like structures, with very low resistivity (<10 ohm m) could be associated to small convective cells is confirmed by the sensitivity analysis carried out in the present study. Those structures are the most likely candidates for a detailed analysis in order to determine their geothermal economic potential. A comprehensive review of existing geophysical data and models of Gran Canaria island and their comparison with the new 3D electrical resistivity model is presented.